PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN IPAS DI KELAS V SDN 107405 SEI ROTAN T.A 2024/2025 - Nurasnaini; Nurmayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the feasibility, practicality, and effectiveness of a pop-up book learning media based on local wisdom for IPAS (Science and Social Studies Integration) learning in Grade V at SDN 107405 Sei Rotan. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the product was determined through expert validation, with material expert validation scoring 85.8%, categorized as "highly feasible," and media expert validation scoring 92%, also categorized as "highly feasible." The practicality assessment by a practitioner expert showed a percentage of 92%, falling into the "highly practical" category. The effectiveness of the media was measured through students' learning outcomes by comparing pre-test and post-test results, analyzed using the N-Gain Score, which reached 78.38%, categorized as "highly effective." Therefore, it can be concluded that the pop-up book learning media based on local wisdom for IPAS learning in Grade V at SDN 107405 Sei Rotan is highly feasible, highly practical, and highly effective for use in elementary school learning.